CORRELATION BETWEEN ADENOSINE DEAMINASE ACTIVITY IN PLEURAL FLUID AND SERUM OF PATIENTS WITH PLEURAL EFFUSION - Pande Putu Ayu Patria Dewi; Aryati Aryati; Leonita Anniwati; Isnin Anang Marhana (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Pleural effusion is an abnormal accumulation of fluid in the pleural space resulting from increased production of fluid or decreased resorption of fluid in the pleural space. Pleural effusion can be caused by infectious diseases, malignancies, collagen disease, gastrointestinal disease, heart disease and other causes such as medication. Adenosine Deaminase (ADA) is an enzyme involved in the catabolism of purines. This enzyme can be measured in pleural fluid, serum and other body fluids such as cerebrospinal and ascites fluid. The aim of this study was to analyze the correlation between adenosine deaminase activity in pleural fluid and serum in patients with pleural effusion. This research was an observational study with a cross-sectional design. Examination of ADA activity was performed in pleural fluid and serum. Adenosine deaminase activity was examined using photometric methods (Non-Giusti), using Diazyme reagent by TMS 24i Premium. Subjects were 46 patients with pleural effusion caused by malignancies, tuberculosis and systemic diseases. Mean±SD ADA activity for all pleural effusion samples in serum was 13.037± 8.365 (0.5-34.1) U//L and pleural fluid 30.843± 28.860 U//L (1.3-140.8). No correlation between ADA activity in serum and pleural fluid (r=0.173, p= 0.252) was found in all samples. No correlation between ADA activity in serum and pleural fluis was found in malignancies (r=0.109, p=0.630), tuberculosis (r= 0.366, p=0.123), systemic diseases (r =0.466, p=0.429) and non-tuberculosis group (r=0.126, p=0.532). There was no correlation between pleural fluid ADA activity and serum.